External Carotid Ligation in Extensive Haemangioma of Tongue & Lip - Rahman, MM; Rashid, MM; Rahman, MA; Khan, SA; Islam, MF; Reza, ME (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 217-220 The abstract of this article is available on the PubMed website